Robot-aided thoracoscopic thymectomy for early-stage thymoma: A multicenter European study - Marulli, Giuseppe; Rea, Federico; Melfi, Franca; Schmid, Thomas A.; Ismail, Mahmoud; Fanucchi, Olivia; Augustin, Florian; Swierzy, Marc; Di Chiara, Francesco; Mussi, Alfredo; Rueckert, Jens C. (The Journal of thoracic and cardiovascular surgery, 2012)
Minimally invasive thymectomy for stage I to stage II thymoma has been suggested in recent years and considered technically feasible. However, because of the lack of data on long-term results, controversies still exist on surgical access indication. We sought to evaluate the results after robot-assisted thoracoscopic thymectomy in early-stage thymoma. Data were collected from 4 European centers. Between 2002 and 2011, 79 patients (38 men and 41 women; median age, 57 years) with early-stage thymoma were operated by left-sided (82.4%), right-sided (12.6%), or bilateral (5%) robotic thoracoscopic approach. Forty-five patients (57%) had associated myasthenia gravis. Average operative time was 155 minutes (range, 70-320 minutes). One patient needed open conversion, in 1 patient a standard thoracoscopy was performed after robotic system breakdown, and in 5 patients an additional access was required. No vascular and nervous injuries were recorded, and no perioperative mortality occurred. Ten patients (12.7%) had postoperative complications. Median hospital stay was 3 days (range, 2-15 days). Median diameter of tumor resected was 3 cm (range, 1-12 cm), and Masaoka stage was stage I in 30 patients (38%) and stage II in 49 patients (62%). At a median follow-up of 40 months, 74 patients were alive and 5 had died (4 patients from nonthymoma-related causes and 1 from a diffuse intrathoracic recurrence), with a 5-year survival rate of 90%. Our data indicate that robot-enhanced thoracoscopic thymectomy for early-stage thymoma is a technically sound and safe procedure with a low complication rate and a short hospital stay. Oncologic outcome seems good, but a longer follow-up is needed to consider this as a standard approach definitively.